Strategi Transformatif Perpustakaan Tingkat Desa dalam Gerakan Literasi Nasional - Asichul In'am (Asosiasi Dosen Tarbiyah STAI Darussalam Nganjuk, 2020)
The village library is one type of public library that is a place to attract users who are in the village environment and have a very important role. People who have a desire to read, while their reading material is incomplete, this library will be the support for that desire. As for the government’s efforts to foster literacy throughout the archipelago, one of which is the national literacy movement. There are six dimensions that have become the benchmarks for this national literacy movement, including: (1) reading and writing literacy (2) numeracy literacy (3) scientific literacy (4) digital literacy (5) financial literacy (6) cultural and civic literacy. These six dimensions are tools used by the government to develop and deepen knowledge for society. The transformative strategy of village libraries in realizing this national literacy movement includes, (1) virtual or digital library collections, (2) providing services in the form of mobile libraries, (3) promoting to users